Efficacy of Colour Doppler Ultrasound in Diagnosis of Cervical Lymphadenopathy - Naik, Raghavendra Mahadev (Springer-Verlag, 2012)
OBJECTIVES: The purpose of the study was to evaluate the efficacy of colour doppler ultrasound (CDUS) in diagnosis of cervical lymphadenopathy. MATERIALS AND METHODS: The study group consisted of 30 patients with clinical evidence of cervical lymphadenopathy (19 patients with clinically suspected reactive/benign cervical lymphadenopathy and 11 patients with clinically suspected malignant/metastatic cervical lymphadenopathy). CDUS examinations were carried out for one lymph node (LN) in each patient and fine needle aspiration cytology of the same LN was obtained. To evaluate the efficacy of CDUS, comparison between clinical features, CDUS features and cytological features of enlarged cervical LNs were then done. RESULTS: Clinical examination evaluated 54 cervical LNs. CDUS evaluation discovered an additional 55 LNs (54 + 55 = 109). Accuracy of the CDUS examination was higher than clinical evaluation. Patterns of colour doppler flow signals when correlated with cytological diagnosis showed central flow for benign nodes and peripheral flow for malignant nodes. The mean pulsatility index (PI) was 1.977 ± 0.669 in LNs involved with metastases and 0.839 ± 0.135in LNs affected by benign processes. LNs involved with metastases showed a characteristic high resistive index (RI) and a high pulsatility index than the lymph nodes affected by benign processes. The RI and PI were significantly different between LNs affected by benign versus malignant disease. CONCLUSION: Nodal vascularity of the LNs can be used to differentiate benign from malignant lymphadenopathy. CDUS can be trusted upon as a reliable marker for the diagnosis of cervical lymphadenopathy.